Maltotriose transport and utilization in baker's and brewer's yeast - Michaljanicová, D; Hodan, J; Kotyk, A (Folia microbiologica, 1982)
Maltotriose is metabolized by baker's and brewer's yeast only oxidatively, with a respiratory quotient of 1.0, the QCO2Ar being, depending on the strain used, 0-11, as compared with QCO2air of 6-42 microL CO2 per h per mg dry substance. The transport appeared to proceed by facilitated diffusion (no effects of NaF, iodoacetamide and 3-chlorophenylhydrazonomalononitrile) with a KT of more than 50 mM and was inhibited by maltose greater than maltotriose greater than methyl-alpha-D-glucoside greater than maltotetraose greater than D-fructose greater than D-glucose. The transport was present constitutively in both Saccharomyces cerevisiae (baker's yeast) and in S. uvarum (brewer's yeast) and it was not significantly stimulated by preincubation with glucose or maltose. The pH optimum was 4.5-5.5, the temperature dependence yielded an activation energy of 26 kJ/mol.
Keywords: Biological Transport; Saccharomyces cerevisiae; biologický transport; Trisaccharides; oligosacharidy; trisacharidy; spotřeba kyslíku; Oxygen Consumption; Oligosaccharides; Saccharomyces